COVID-19 incidence in a cohort of public transport workers - De Matteis, Sara; Cencedda, Valerio; Pilia, Ilaria; Cocco, Pierluigi (La Medicina del Lavoro, 2022)
Background: Previous research has shown an excess risk of COVID-19 among several occupations, but data on public transport workers are scarce. To investigate the occupational risk posed by contact with the public, we followed up the incidence of COVID-19 in a cohort of public transport workers. Methods: We identified the incident cases of COVID-19 between 1 September 2020 - 6 May 2021 in a cohort of 2,052 employees of a public transport agency in Sardinia, Italy. The diagnosis of COVID-19 was based on a positive molecular test. To calculate the expected events, we applied the age- and gender-specific incidence rates of the regional population in the same time period to the correspondent strata of the study cohort. We estimated the relative risk (RR) of COVID-19 as the ratio between the observed and the expected events and its 95% confidence interval (95% C.I.) among the total cohort and in two sub-cohorts: bus drivers, and the rest of the personnel (administrative staff, train and metro drivers, workers in the mechanical shop, and in the railroad maintenance, and security). Results: Bus drivers run an elevated risk of COVID-19 (RR = 1.4, 95% C.I. 1.07 - 1.79). There was no excess risk among the sub-cohort including the rest of the personnel. Conclusions: Our study suggests an excess risk of COVID-19 among bus drivers even in a relatively low incidence area, which could imply inadequacy of the preventive measures in place. Further, larger size studies with detailed information on personal and lifestyle characteristics are warranted.